Overburden Geochemistry and Acid Rock Drainage Scale-Up Investigations at the Grasberg Mine, Papua Province, Indonesia - J Andrina; D Richards (The Australasian Institute of Mining and Metallurgy, 2003)
The Grasberg is a large copper and gold open pit mine operated by PT Freeport Indonesia and located in the high equatorial mountains of Papua Province, Indonesia. The climate is alpine/sub-alpine with little seasonal variation in temperature and rainfall. The annual precipitation varies from about 3000 to 5000 mm over short distances around the Grasberg, but in general, an average daily precipitation of 10 mm per day applies and leaching of the overburden is continuous throughout the year. Mining commenced in 1988, and almost all of the overburden mined up to 2003 was potentially acid forming. The current acid drainage from this overburden is being collected and treated. From 2004 to the end of the Grasberg pit operation in 2014, approximately 70 per cent of the overburden will be potentially acid forming and 30 per cent limestone. A program of laboratory leach columns, field test pads and an instrumented full-scale dump was developed with the objective of defining scale up factors to quantify the acid and metal leaching rates and to evaluate the stockpile geochemistry and control options. The results of an ongoing seven year program have demonstrated feasible scale up between laboratory columns, field test pads and the trial dump in relation to material geochemistry and ARD evolution trends at Grasberg. The potentially acid forming waste types are highly reactive and maximum acid generation rate occurs within two to three years and that maximum copper release occurs within one to two years of exposure. The results also show that the net acid generation (NAG) test provides a good estimate for the potential acid load from overburden types. The chemistry, temperature and oxygen data from the trial dump suggest that oxidation and acid generation is occurring throughout the dump but at a decreasing mass rate with increasing distance from the toe of the dump. It is apparent that convection and/or advection are important mechanisms for the transport of oxygen into and within the dump. Key results and findings of the investigations carried out are presented and the implications of the findings for long-term ARD management at the Grasberg mine are outlined.